STUDIO DI ALCUNE COLONNE GRANITICHE DELLA CITTA' ROMANA DI UTHINA (TUNISIA) E SULLE LORO ANTICHE CAVE DEL NORD SARDEGNA - Cara Stefano; Matzuzzi Carlo (Zenodo, 2015)
This paper presents a detailed petrochemical and minerochemical study on some Roman granite columns from the archaeological site of Uthina. An ancient roman city located about 30km SW from Tunis (Tunisia), near the village of Oudhna. Some of the sampled columns show a very similar macroscopic aspect to the pinkish-grey granites outcropping in the ancient quarry area of Capo Testa, in northern Sardinia (Italy). In order to provide a comparison between the archaeological samples and the granite of these quarries a detailed geo-archeological survey and sampling of the Capicciolu, Li Petri Taddati, Cala Romana, Cava Grande del Torre "loci" (Capo Testa peninsula) and of the two La Marmorata Island "loci" were carried out. The results of the analyses showed that three of the sampled columns (these pinkish-grey in colour) have a strong resemblance with the samples of La Marmorata quarries. This demonstrates that, during the II-III centuries AD, the granite of North Sardinia quarries had a diffusion beyond the regional limits, confirming the identification of several granite artifacts discovered in monuments of the ancient Rome and in some other cities of the North Africa provinces.